2022
DOI: 10.1161/hypertensionaha.122.19207
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Antagonism by Finerenone Attenuates Established Pulmonary Hypertension in Rats

Abstract: Background: We studied the ability of the nonsteroidal MR (mineralocorticoid receptor) antagonist finerenone to attenuate vascular remodeling and pulmonary hypertension using two complementary preclinical models (the monocrotaline and sugen/hypoxia rat models) of severe pulmonary hypertension. Methods: We first examined the distribution pattern of MR in the lungs of patients with pulmonary arterial hypertension (PAH) and in monocrotaline and sugen/hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Those experimental studies have employed MRAs spironolactone, eplerenone, or finerenone in several models of PH ( Tables 1 , 2 ). The overall finding of those studies is that MRAs can prevent and partially reverse pulmonary vascular remodeling and improve pulmonary hemodynamics in PH ( 43 , 47 , 51 53 ) ( Tables 1 , 2 ). Preventive application MRAs attenuated the development of adverse pulmonary vascular remodeling as assesses by attenuated PA muscularization and wall thickening along with decreased PA pressure ( 27 , 44 , 46 , 47 , 51 , 52 , 54 ) ( Table 1 ).…”
Section: Pharmacological Targeting Of Mr In Ph Animal Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Those experimental studies have employed MRAs spironolactone, eplerenone, or finerenone in several models of PH ( Tables 1 , 2 ). The overall finding of those studies is that MRAs can prevent and partially reverse pulmonary vascular remodeling and improve pulmonary hemodynamics in PH ( 43 , 47 , 51 53 ) ( Tables 1 , 2 ). Preventive application MRAs attenuated the development of adverse pulmonary vascular remodeling as assesses by attenuated PA muscularization and wall thickening along with decreased PA pressure ( 27 , 44 , 46 , 47 , 51 , 52 , 54 ) ( Table 1 ).…”
Section: Pharmacological Targeting Of Mr In Ph Animal Modelsmentioning
confidence: 99%
“…Beside indirect signaling via MR in PAECs, it has been shown that MR activation in PASMCs is involved in PH progression. A recent study has provided direct experimental evidence that MR is overexpressed in PASMCs of the remodeled PAs in patients with PAH as well as in monocrotaline and hypoxia-sugen rats with established PH ( 43 ). In vitro , aldosterone activates MR in PASMCs in a dose-dependent manner without affecting its expression level ( 44 ).…”
Section: Aldosterone–mr Signaling In Pulmonary Vascular Cellsmentioning
confidence: 99%
See 3 more Smart Citations